2018
DOI: 10.1680/jmacr.16.00108
|View full text |Cite
|
Sign up to set email alerts
|

Equation for stress–strain relationship of recycled aggregate concrete in axial compression

Abstract: The experimentally observed behaviour of normal-strength recycled aggregate concrete made with varying amounts of coarse recycled concrete aggregate (RCA) in uniaxial compression was modelled using a single polynomial-based equation valid for both the ascending as well as the descending branches of the stress–strain relationship. The measured stress–strain relationships of companion cylindrical specimens were averaged using a simple procedure that was found to be effective. The proposed constitutive model refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The σ p of RAC with replacement ratios of 20%, 40%, 60%, 80% and 100% were 15.2%, 10.6%, 17.1%, 20.3% and 27.4% lower than that of NAC, respectively, and the corresponding ε p of RAC with replacement ratios of 20%, 40%, 60%, 80% and 100% were −0.8%, 3.8%, 9.4%, 16.8% and 25.6% higher than that of NAC, respectively. Suryawanshi et al [ 18 ], Xiao et al [ 20 ], Belén et al [ 21 ] and Luo et al [ 44 ] revealed a similar conclusion that the σ p of uncarbonated RAC was no more than 30% lower than that of NAC, and the ε p of RAC was no more than 25% higher than that of NAC. It was because with increasing content of RCA, in addition to the rising number of cracks inside mortar and ITZ, the effective water-cement ratio around RCA was larger than that around NCA due to the adopted prewetting method before mixing, thus leading to a decrease in σ p .…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The σ p of RAC with replacement ratios of 20%, 40%, 60%, 80% and 100% were 15.2%, 10.6%, 17.1%, 20.3% and 27.4% lower than that of NAC, respectively, and the corresponding ε p of RAC with replacement ratios of 20%, 40%, 60%, 80% and 100% were −0.8%, 3.8%, 9.4%, 16.8% and 25.6% higher than that of NAC, respectively. Suryawanshi et al [ 18 ], Xiao et al [ 20 ], Belén et al [ 21 ] and Luo et al [ 44 ] revealed a similar conclusion that the σ p of uncarbonated RAC was no more than 30% lower than that of NAC, and the ε p of RAC was no more than 25% higher than that of NAC. It was because with increasing content of RCA, in addition to the rising number of cracks inside mortar and ITZ, the effective water-cement ratio around RCA was larger than that around NCA due to the adopted prewetting method before mixing, thus leading to a decrease in σ p .…”
Section: Resultsmentioning
confidence: 78%
“…In previous studies, researchers were devoted to the investigation on the stress–strain relationship of RAC and proposed corresponding models [ 18 , 20 , 21 ]. The model proposed by Guo [ 45 ] was used to describe the stress–strain curves of RAC after carbonation.…”
Section: Fitting Analysis Of Stress–strain Relation Of Rac After Carbonationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies were conducted on the behavior of concretes containing RCA (e.g., References 10–17). As was mentioned in literature, mechanical strength and durability characteristics of concretes having RCA were generally inferior in comparison with those without RCA 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a great deal of research has been carried out to develop RAC worldwide. The material property of recycled aggregate (Wang, Hsiao, and Wang 2012;Bravo et al 2015), the mechanic performance of RAC under the static loadings (ACI Committee 555, 2002), and the constitutive relationship of stress-strain of RAC under the static loadings (Xiao, Li, and Zhang 2005;Suryawanshi, Singh, and Bhargava 2018) are experimentally studied and theoretically analyzed. It has been found that there is a slight difference in mechanical properties between recycled aggregate concrete (RAC) and natural aggregate concrete (NAC) because of the variability and randomness of waste concrete from disparate sources.…”
Section: Introductionmentioning
confidence: 99%